2023
DOI: 10.3389/fgene.2022.1090640
|View full text |Cite
|
Sign up to set email alerts
|

The gene signature of tertiary lymphoid structures within ovarian cancer predicts the prognosis and immunotherapy benefit

Abstract: Ovarian cancer (OC) has the lowest survival rate among gynecologic malignancies. Ectopic lymphocyte aggregates, namely tertiary lymphoid structures (TLSs), have been reported as positive biomarkers for tumor prognosis. However, the related gene signature of tertiary lymphoid structure in ovarian cancer was less understood. Therefore, this study first exhibited the organizational patterns of tertiary lymphoid structure by H&E staining and immunohistochemistry (IHC), and confirmed the improved survival v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…This results that the higher the LAMP3 expression, the better prognosis does not conform to conventional thinking. In OV, the high expression group of tertiary lymphoid structures (TLSs) including the LAMP3 gene exhibited a favourable prognosis for OS and this result is consistent with our database analysis 29 . LAMP3 was reported to be sharply related to locoregional control in patients who received radiation therapy 27 .…”
Section: Discussionsupporting
confidence: 84%
“…This results that the higher the LAMP3 expression, the better prognosis does not conform to conventional thinking. In OV, the high expression group of tertiary lymphoid structures (TLSs) including the LAMP3 gene exhibited a favourable prognosis for OS and this result is consistent with our database analysis 29 . LAMP3 was reported to be sharply related to locoregional control in patients who received radiation therapy 27 .…”
Section: Discussionsupporting
confidence: 84%
“…In the case of the two subclones present in patient 5, single-cell resolution spatial transcriptomics with CosMx SMI revealed both were highly infiltrated by CCL5 +T cells, C1QC+ and CXCL9+ macrophages. Notably, these cells formed clusters resembling tertiary lymphoid structures which have been reported as predictive of prognosis in HGSOC 51 (Fig. 4e ).…”
Section: Discussionmentioning
confidence: 62%
“…S5D), we found that plasma cells identified were enriched in PDPN-positive ROIs and that the immune infiltrates in PDPN-positive ROIs were enriched in genes associated with plasma cell differentiation and/or recruitment (JCHAIN, CD38, IGHG3, CD79A, SLAMF7, IGKC, PRDM1, and XBP1; fig. S5E), while the immune infiltrates in PDPN-negative ROIs were enriched in genes typically associated with T and B cells in mature TLSs (CXCL13, MS4A1, CD8A, CD3D, CD3E, CCL19, TRBC1, CD2, CXCL9, and CCR7) ( 61 ). As an independent validation method for the expression of different cytokines and chemokines and their receptors in PDPN-positive and TLS-positive areas, we stratified patients with ovarian cancer in The Cancer Genome Atlas (TCGA) into PDPN High TLS Low and PDPN Low TLS High based on the expression of PDPN and the TLS gene signature ( 62 ).…”
Section: Resultsmentioning
confidence: 99%